The Multimedia Development for Learning Outcomes of Fraction Concept in Third Grade Of SDN 41 Sungai Ambawang - Mahdalena Mahdalena; Indri Astuti; Dede Suratman (JP2D (Jurnal Penelitian Pendidikan Dasar) UNTAN, 2019)
The main problem in this research is the difficulty of learning media procurement in math, especially on fractional concept material. Many learners have difficulty understanding fractions because learning tends to use a mechanistic way of giving rules directly to be memorized, remembered, and applied so that learners will quickly forget the fractional concepts, and it will be challenging to apply the concept. The results of this research are: (1) multimedia design is carried out through stages such as conducting preliminary research, designing, material collection, initial product development, material expert validation, media expert and design expert, (2) multimedia profile depicted in the storyboard contains the forms of drawings accompanied by explanations or narratives used in the process of producing multimedia programs, so that in the process of producing multimedia programs will be more structured and orderly, (3) students implement multimedia learning with enthusiasm, it looks more enthusiastic learners in the implementation of learning so that learners are more independent and active, and (4 Learning outcomes of learners who use multimedia, this can be seen from the differences in learning results fractional concepts between before learning and after learning to use multimedia.